Fertilizing Treatment of Soybean Anjasmoro Varieties on Rainfed Rice Field in Water Shortages Areas of Pidie Regency - Helmi Helmi; Munawar Khalil; Ilyas Ilyas; Teuku Makmur; Edy Marsudi; Akhmad Baihaqi (Serambi Journal of Agricultural Technology, 2021)
Appropriate fertilization in the cultivation of high-yielding varieties has a great opportunity to increase soybean production, especially in soybean centers where areas lack water and ex-paddy fields. An assessment was conducted in Ujong Pie Village, Muara Tiga District, Pidie Regency during the 2020 dry season. The study demonstrated the use of appropriate cultivation technology and superior varieties of Anjasmoro soybean. Plants are managed with integrated crop management (PTT). The land used is land that was previously used for rice planting activities. The study applied five treatments, namely the former fertilized N (P1), K (P2), P (P3), and NPK (P4), as well as the pattern of farmers as control (P5). Pest and disease control is carried out with the principle of IPM. The variables measured were the growth rate of plants and their production components. The results obtained showed that the average plant height during the vegetative period at locations P4 and P5 (P0.05) was higher than those who received other treatments. The maximum growth (height) of plants that received the treatment were 56.33 cm and 54.66 cm. The highest average number of pods per plant occurred in plot P5 and then in P4, 16.50 and 15.00 pods per plant, respectively. The highest average seed production per plant was achieved in plot P5 (18.4 g/plant) and followed by plot P4 (17.13 g/plant) or converted in hectares with an average of 1.82 t/ha and 1, 50 t/ha